Environmental correlates for tropical tree diversity and distribution patterns in Borneo - Slik, J.W.F.; Raes, N.; Aiba, Shin-Ichiro; Brearley, F.Q.; Cannon, Charles H.; Meijaard, E.; Nagamasu, H.; Nilus, R.; Paoli, G.; Poulsen, A.D.; Sheil, Douglas; Suzuki, E.; et al. (2009)
A GIS-environmental database with 5 arc minute (c. 10 x 10 km) resolution was combined with tree inventory data. Tree diversity, phylogenetic diversity (PD) and the two main compositional gradients were determined for 46 tree inventories. Akaike's information criterion and a data jackknifing procedure were used to select 50 explanatory models for diversity and composition gradients. The average of these models was used as our final diversity and compositional model. We applied Moran's I to detect spatial autocorrelation of residuals. Tree diversity, PD and the two main compositional gradients in Borneo were all significantly correlated with the environment. Tree diversity correlated negatively with elevation, soil depth, soil coarseness (texture) and organic carbon content, whereas it correlated positively with soil C:N ratio, soil pH, moisture storage capacity and annual rainfall. Tree PD was correlated positively with elevation and temperature seasonality and was largely determined by gymnosperms. However, angiosperm PD also correlated positive with elevation. Compositional patterns were strongly correlated with elevation but soil texture, cation-exchange-capacity, C:N ratio, C and N content and drainage were also important next to rainfall seasonality and El Nino Southern Oscillation drought impact. Although elevation is the most important correlate for diversity and compositional gradients in Borneo, significant additional variability is explained by soil characteristics (texture, carbon content, pH, depth, drainage and nutrient status) and climate (annual rainfall, rainfall seasonality and droughts). The identified environmental correlates for diversity and composition gradients correspond to those found in other tropical regions of the world. Differences between the regions are mainly formed by differences in the relative importance of the environmental variables in explaining diversity and compositional gradients.